Legal Protection Against Children as Intermediary of Purchase of Narcotics at Polewali Mandar Police Resort Area (Case Study Year 2013-2015) - Yulianti, Anisa; Al Magfur, Muhammad Rokhi (Jurnal Scientia Indonesia, 2019)
The problem of narcotics abuse in Indonesia is now felt in an alarming situation. Narcotics abuse by children today is the concern of many people and is constantly being discussed and published. Indonesia has participated in participating in tackling the crime of narcotics abuse, namely the legislation of Law Number 35 Year 2009 on Narcotics. Factors that cause the child to mediate the sale and purchase of narcotics in polewali polarization polarization area due to family factors, environmental factors and economic factors. Efforts made by law enforcement officers, especially the Police in tackling the crime of narcotics circulation involving children as intermediaries of buying and selling, namely: prevention efforts (preventive) by providing counseling in the community and schools about narcotics, conduct raids and patrols regularly, (repressive), and coaching efforts to keep the future of the child can remain good. From this writing shows that children who commit narcotics crime, especially as narcotics courier, can be charged with Law number 35 of 2009 on Narcotics by not ruling out the special provisions set forth in Law Number 11 of 2012 on the Criminal Justice System of Children.